Seismic Design of Steel Structures with Special Flexural Frame Based on Performance by Durability Method - Pouyan Ashrafzadeh; Arash Kheyrolahi (Salehan Institute of Higher Education, 2018)
Equivalent static, response spectrum and time history analysis are the well-known analysis methods that traditionally proposed. These methods are highly accurate but requires a great deal of time to match accelerations and the number of analyses, in the other words these methods are time consuming methods. Hence recently the structures are investigated using the durability time method, which plays an essential role in reducing the number of analyses that needs to be created; In fact, the durability time method is a new method of seismic analysis that is presented with a minimum number of time histories analysis. In this method the structure is placed under the influence of an increasing dynamic stimulation, structural response has been investigated over time and evaluated according to the corresponding response to different levels of stimulation intensity, strengths and weaknesses, and structural performance. In this study, steel folding frameworks with 5, 10 and 15 floors were investigated under two analytical methods (Time durability and Time histories methods). At first, the frameworks will be exposed under history of Imperial Governor, Kobe and Lumaprita earthquakes and analysis by finite element software ABAQUS. Then, based on the three analytical functions, the durability is investigated and the results are compared with each other. Finally, the behavior of the structures discussion and conclusion. The results show that the durability analysis method for earthquakes with higher intensity and time is more efficient, and for the Time-less earthquakes by time history method parametrically have a parametrical difference of 5%.